Implementasi Manajemen Sumber Daya Manusia untuk Meningkatkan Kinerja Guru di SMP IT Imam Syafi’I dan Insan Utama Pekanbaru - Sri Murhayati; Zamsiswaya Zamsiswaya; Khoironi Khoironi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Abstrak: This study aims to see how the implementation of human resource management to improve teacher performance and what factors encourage and hinder human resource management in improving teacher performance at Integrated Islamic Junior High Schools in Marpoyan Damai District, Pekanbaru City. This research was limited to 2 schools, namely Imam Syafii IT Middle School and Main Insan. This type of research uses descriptive qualitative. The informants in this study were 2 school principals and 40 teachers. Data collection techniques in this study using observation, interviews and documentation. The results of this study show that the implementation of human resource management to improve teacher performance at Integrated Islamic Junior High Schools in Marpoyan Damai District, Pekanbaru City is quite good, evidenced by human resource planning (HR) based on needs, human resource recruitment must be Strata qualifications 1 (S-1), Recruitment of human resources (HR) is carried out to increase the number of workers, and placement of human resources (HR) is carried out so that empty lesson hours are filled with learning activities. Then the driving factor for human resource management in improving teacher performance at SMP IT Imam Syafii and Insan Utama, namely the amount of support from student guardians, students and school principals, collaboration with other institutions, and training programs. While the inhibiting factors are: limited learning time, less optimal education and teacher training development, and personal busyness of each board so that they cannot carry out their duties on time.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//